Dietary intakes of trans fatty acids before the prohibition of partially hydrogenated oils in Canada - Demonty, Isabelle; Wang, Kuan Chiao; Rondeau, Isabelle; Martineau, Chantal; Manley, Lindsay; Daoust, Janice; Hopperton, Kathryn (European journal of nutrition, 2025)
Purpose Canada’s public health objective is that ≥ 90% of the population consume <1% of total energy (< 1%En) as trans fatty acids (TFA), in line with World Health Organization recommendations. Our study aimed to estimate usual intakes of total TFA, industrially-produced TFA (i-TFA), and naturally occurring TFA (n-TFA) overall and in subgroups of the population before Canada’s 2018 prohibition on the use of partially hydrogenated oils (PHO) in foods. Methods Data from 1–2 24-h recalls was available for 19,670 participants in the cross-sectional Canadian Community Health Survey (CCHS)—Nutrition 2015. Usual intakes of total TFA, i-TFA, n-TFA, and mixed TFA (TFA from foods containing both i-TFA and n-TFA) from all foods and beverages were generated according to the National Cancer Institute method, and weighted to represent the population of Canada aged ≥ 1 and within age, sex, income, and self-reported racial groups. Results For the overall population, the mean usual intake of total TFA was 1.2 g/day (SE:0.02) and represented 0.57%En (SE:0.001). All age-sex groups had mean total TFA intakes <1%En, ranging from 0.52 to 0.71%En. On average, foods containing only n-TFA provided >1/2 of total TFA intake (0.32%En, SE:0.01). The target of ≥ 90% of the population consuming <1%En as TFA had already been achieved before the PHO prohibition in all income, racial, and age-sex groups, except children 1–3 years old, with 86% within target. In that group, foods containing only n-TFA provided >2/3 of total TFA intake (0.48%En, SE:0.02). Conclusion Total TFA intakes in Canada before the PHO prohibition were relatively low, likely due to previous initiatives to reduce i-TFA in foods.